2020
DOI: 10.3748/wjg.v26.i33.4960
|View full text |Cite
|
Sign up to set email alerts
|

Effects of denosumab treatment in chronic liver disease patients with osteoporosis

Abstract: BACKGROUND Effective treatment of osteoporosis is essential for improving morbidity and health-related quality of life in chronic liver disease (CLD) patients. Denosumab has been shown to increase bone mineral density (BMD) and decrease the risk of osteoporotic fracture in the general population. However, there are few reports evaluating the efficacy of denosumab in CLD patients. AIM To investigated the effects and safety of denosumab in CLD patients with osteoporosis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 44 publications
(54 reference statements)
0
12
0
2
Order By: Relevance
“…Similarly, treatment with parathyroid hormone (1–34) induced enzymatic collagen cross-links, increased bone volume, and decreased pentosidine (non-enzymatic cross-links) levels in monkeys with ovariectomy, thereby improving bone strength [ 35 ]. We previously reported that administration of denosumab, a human monoclonal antibody against the receptor activator of nuclear factor kappa-B ligand, increased BMD, suppressed bone turnover, and decreased plasma pentosidine in CLD patients with osteoporosis [ 36 ]. The current clinical practice guidelines on CLD recommend supplementation with calcium and vitamin D for a T-score < −1.5 and administration of bisphosphonates to improve BMD in CLD patients with osteoporosis [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, treatment with parathyroid hormone (1–34) induced enzymatic collagen cross-links, increased bone volume, and decreased pentosidine (non-enzymatic cross-links) levels in monkeys with ovariectomy, thereby improving bone strength [ 35 ]. We previously reported that administration of denosumab, a human monoclonal antibody against the receptor activator of nuclear factor kappa-B ligand, increased BMD, suppressed bone turnover, and decreased plasma pentosidine in CLD patients with osteoporosis [ 36 ]. The current clinical practice guidelines on CLD recommend supplementation with calcium and vitamin D for a T-score < −1.5 and administration of bisphosphonates to improve BMD in CLD patients with osteoporosis [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Denosumab is a human monoclonal antibody for RANKL and mimics the endogenous effect of OPG, thereby inhibiting bone resorption and remodeling. Our study of CLD patients with osteoporosis revealed that denosumab increased BMD, suppressed bone turnover, and improved a bone quality marker after 12 months of treatment [ 155 ]. Meanwhile, RANK is expressed in skeletal muscle, and muscle-specific RANK deletion was protective against denervation-induced loss of muscle force in mice [ 156 ].…”
Section: Osteosarcopenia In Chronic Liver Diseasementioning
confidence: 99%
“…У пацієнток із захворюваннями печінки запропоновано використання різних ліків від остеопорозу, але більшість досліджень включали невелику кількість пацієнток, що обумовлює відсутність консенсусу з цього питання [8,9].…”
Section: полтавський державний медичний університет українаunclassified
“…Бісфосфонати -антикатаболічні препарати, які збільшують кісткову масу та зменшують частоту переломів при постменопаузальному остеопорозі [10]. Їх вплив на перебіг захворювань печінки на сьогоднішній день не повністю визначений в осно-вному через невелику кількість досліджень та невелику кількість пролікованих пацієнток [5,6,8,9] Для включення в дослідження усім пацієнткам виключали наявність вірусних гепатитів В, С, у дослідження включали пацієнток із нормальними значеннями аланін та аспартатамінторансферази для виключення псевдопозитивної діагностики фіброзу печінки внаслідок ущільнення печінкової тканини на фоні запалення. Усі досліджені пацієнтки знаходились у менопаузі із середнім строком 7,8±3,5 років.…”
Section: полтавський державний медичний університет українаunclassified